2003
DOI: 10.1034/j.1600-0897.2003.00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Pro‐inflammatory Maternal Cytokine Profile in Preterm Delivery

Abstract: These data are suggestive of a maternal type 1 cytokine bias in PTD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 42 publications
6
81
1
1
Order By: Relevance
“…Therefore, the secretion of pro-inflammatory cytokines such as IL-1, IL-6, IL-8, and TNFa is increased in amniotic fluid, decidual tissue, and chronic tissue. Although the secretion of Th1-type cytokines, i.e., IL-2, IFNc, and TNFa, which mediate inflammatory reactions, is up-regulated in preterm labor, 50 the secretion of Th2-type cytokines, i.e., IL-4 and IL-6, is also elevated. 51 TGF-b might be a key cytokine that regulates Th17 ⁄ Treg lineage.…”
Section: Th1 ⁄ Th2 ⁄ Th17 and Treg Paradigms In Preterm Labormentioning
confidence: 99%
“…Therefore, the secretion of pro-inflammatory cytokines such as IL-1, IL-6, IL-8, and TNFa is increased in amniotic fluid, decidual tissue, and chronic tissue. Although the secretion of Th1-type cytokines, i.e., IL-2, IFNc, and TNFa, which mediate inflammatory reactions, is up-regulated in preterm labor, 50 the secretion of Th2-type cytokines, i.e., IL-4 and IL-6, is also elevated. 51 TGF-b might be a key cytokine that regulates Th17 ⁄ Treg lineage.…”
Section: Th1 ⁄ Th2 ⁄ Th17 and Treg Paradigms In Preterm Labormentioning
confidence: 99%
“…Although at 48 h a trend was observed in response to AngII treatment toward higher IFN-␥ and lower IL-4 production, the difference between AngII treatment and PHA stimulation alone did not reach statistical significance, which could be due to considerable donor variability. We therefore calculated the IFN-␥:IL-4 ( Figure 2C) for each donor for these two groups as has been done previously (18,19), which demonstrates a significant although modest shift toward greater IFN-␥ production and lesser IL-4 production in response to AngII treatment at 48 h as compared with PHA alone. Of note, the ratio of IFN-␥:IL-4 is thought to be more important in bringing about changes in cytokine signaling, as Th1 and Th2 cytokines are mutually inhibitory (18,19).…”
Section: Angii Treatment Increases the Ratio Of Ifn-␥:il-4 But Not Thmentioning
confidence: 99%
“…We therefore calculated the IFN-␥:IL-4 ( Figure 2C) for each donor for these two groups as has been done previously (18,19), which demonstrates a significant although modest shift toward greater IFN-␥ production and lesser IL-4 production in response to AngII treatment at 48 h as compared with PHA alone. Of note, the ratio of IFN-␥:IL-4 is thought to be more important in bringing about changes in cytokine signaling, as Th1 and Th2 cytokines are mutually inhibitory (18,19). The induction of the inflammatory chemokines CCL2/monocyte chemoattractant protein-1 (MCP-1) and CCL5/RANTES by AngII was also assessed.…”
Section: Angii Treatment Increases the Ratio Of Ifn-␥:il-4 But Not Thmentioning
confidence: 99%
“…Makhseed et al (13) found significantly higher levels of the type 1 and lower levels of the type 2 cytokines in supernatants of activated peripheral lymphocytes from women undergoing preterm delivery, than in those from healthy pregnant women. Furthermore, abortion-prone women who proceeded to have successful pregnancy were more Th2 biased than abortionprone women who aborted (14).…”
Section: P Eripheral Lymphocytes From Healthy Pregnant Women Express mentioning
confidence: 99%